Legend and oral telling in the novel "Polvo y ceniza" - Conde Rivera, Mario (Árboles y Rizomas, 2023)
This article studies seven chapters of the Ecuadorian novel Polvo y ceniza, which make up a narrative block in which several narrators incorporate legend and oral story telling in the literary text. From the theoretical approach of oral narratives, without losing sight of the fact that it is about fictional orality in writing, we analyze how the discourse turns a historical character, Naún Briones, into a legendary figure. Operationally, the analysis comprises two sections that correspond to two distinctive characteristics of oral narratives: the referentiality of events in historical time and the recreation and updating of cultural values and beliefs. The analysis of the first reveals that, in general, an ambiguous referentiality gives rise to historical inaccuracies on which the legendary recreation of the protagonist is built. The analysis of the second, on the other hand, identifies narrators who refer to the facts from their individual experiences; however, through fictional orality, they nuance and expand their stories with collective versions that reflect cultural values and beliefs. Polvo y ceniza, in short, incorporates narrations from oral tradition into literary discourse that oppose the official history.
Keywords: Ecuadorian novel; fictional orality; oral tradition; legend; oral story-telling